Execution's doorstep: true stories of the innocent and near damned - Lytle, Leslie (Northeastern University Press [u.a.], 2008)
Ron Keine -- Juan Robert Melendez -- Michael Ray Graham, jr -- Madison Hobley -- Randal Padgett